THE RELATION BETWEEN TEACHING STRATEGIES WITH TEXTBOOK ANDTHE CURRICULUM: A CASE STUDY AT SMAN I JOGOROGO, NGAWI - RAHAYU, ARUM PUTRI (2010)
The focus of the research is to describe whether the textbook is compatible with the 2006 curriculum or not. The objective of this research is: (1) to know the relevancies between teaching strategies with textbook and curriculum, (2) to know what are the supporting and constraining factors of the compatibility between teaching strategy with textbook and curriculum, (3) to know how is the implementation of the teaching strategy with textbook and curriculum and (4) to know what skills are suggested by the curriculum developed on the English textbook. The research was conducted at Sekolah Menengah Atas Negeri 1 Jogorogo, Ngawi. East Java Province from November 28th until December 28th 2010. It is qualitative research in the form of case study. The object of research is the compatibility between teaching strategies with textbook and curriculum. The data of this thesis was gained from several techniques including in-depth interviewing as the main source in developing and conducting the research, and also classroom observation and documentation. In analyzing the qualitative data the researcher used different ways for deriving the theory, for example, Nurgiyantoro's and Hunchinson and Water's theory. The result of the research finds that the textbook is compatible with the curriculum and it has some constraining factors, namely: (1) the lack of students intake; (2) the lack of learning facility; (3) the students' low human resources; (4) the textbook language organization is difficult to be understand; (5) the publisher does not put the right skills on the right semester. However, in the other hand the research finding reveals that the relation between teaching strategy with the textbook and curriculum has some supporting factors too. Those are from adoption of the curriculum and teacher's characters, namely: (a) the teacher's creativity; (b) the use of students' work book; (c) textbook as a media for teacher to convey the meaning to the students. Anyhow, in implementing the best teaching strategies which suits the textbook and curriculum the teacher mixes the four steps of learning skills with some methods such as grammar translation method, communicative approach, and contextual teaching and learning. Dealing with skills suggested by the curriculum which developed on the English textbook, there are two skills, namely: language skills and communicative exercise. For language skills there are four skills: listening, speaking, reading and writing. Both listening and speaking skills belongs to good level. The percentage is 60 % for listening and 70 68% for speaking. For reading skill the percentage is 90, 90 % and it belongs to very good level; and the last, for writing the percentage is 50 % and it belongs to fairly good level. For the communicative exercise, the percentage is 80 % and it means the skill is good.